Validation of TLC densitometry method for the quantitative determination of alkaloid in fermented endophytic fungi extract Phyllantus niruri Linn - Rollando rollando; Sandra Dewi Tansil; Eva Monica; Yuyun Yuniati; Leny Yuliati (Universitas Ahmad Dahlan, 2019)
Endophytic fungi can produce compound that similar with the host, so it can be used as mass production of compound. The optimal and valid assay method is needed to obtain the proper culture condition, which one using densitometric Thin Layer Chromatography (TLC). This research used 11 samples of endophytic fungi culture extract from Phyllantus niruri within various culture condition. Optimization of mobile phase was done using 3 kinds of mobile phase mixture, chloroform: ethyl acetate: methanol (8:8:4); chloroform: ethyl acetate: methanol: NH4OH (8:8:4:0.005); chloroform:ethyl acetate:NH4OH (8:8:0.005). Validation method measured using some parameters such as linearity, accuracy, and precision. The result of optimization and validation showed that TLC densitometry method can be used for measuring alkaloid level within the endophytic fungi extract of P. niruri using chloroform: ethyl acetate: NH4OH (8:8:0.005), with R value is 0.977, percentage of recovery is between 90–110, and RSD ≤7% on each concentration series. While the proper condition of endophytic fungi culture is using sucrose as carbon source and at pH 6 condition. The content of alkaoid reached 25.9 ± 1.4 mg 100 g-1 fresh weight.